A unified dinucleotide alphabet describing both RNA and DNA structures - Černý, Jiří; Božíková, Paulína; Svoboda, Jakub; Schneider, Bohdan (Nucleic acids research, 2020)
By analyzing almost 120 000 dinucleotides in over 2000 nonredundant nucleic acid crystal structures, we define 96+1 diNucleotide Conformers, NtCs, which describe the geometry of RNA and DNA dinucleotides. NtC classes are grouped into 15 codes of the structural alphabet CANA (Conformational Alphabet of Nucleic Acids) to simplify symbolic annotation of the prominent structural features of NAs and their intuitive graphical display. The search for nontrivial patterns of NtCs resulted in the identification of several types of RNA loops, some of them observed for the first time. Over 30% of the nearly six million dinucleotides in the PDB cannot be assigned to any NtC class but we demonstrate that up to a half of them can be re-refined with the help of proper refinement targets. A statistical analysis of the preferences of NtCs and CANA codes for the 16 dinucleotide sequences showed that neither the NtC class AA00, which forms the scaffold of RNA structures, nor BB00, the DNA most populated class, are sequence neutral but their distributions are significantly biased. The reported automated assignment of the NtC classes and CANA codes available at dnatco.org provides a powerful tool for unbiased analysis of nucleic acid structures by structural and molecular biologists.
Keywords: RNA; Riboswitch; ribozomy; vazebná místa; nukleotidy; Binding Sites; Ribosomes; Nucleotides; reprodukovatelnost výsledků; biokatalýza; DNA; Nucleotide Motifs; riboswitch; Reproducibility of Results; RNA, Catalytic; konformace nukleové kyseliny; Biocatalysis; Nucleic Acid Conformation; nukleotidové motivy; RNA katalytická